Analisis Risiko Keselamatan dan Kesehatan Kerja Pada Tenaga Medis dan Non Medis Estetika di Hayyu Skin Clinic - Dessy Raharyani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze occupational health and safety (OHS) risks among medical and non-medical staff at Hayyu Skin Clinic. The background stems from the lack of a structured OHS management system in aesthetic clinics, exposing workers to physical, chemical, biological, ergonomic, and psychosocial hazards. A qualitative descriptive case study was used, involving observation, in-depth interviews, and document analysis. Data were analyzed thematically using the HIRARC method to assess risk levels. Results revealed significant risks in procedures such as chemical peels, laser treatments, microneedling, and injectable aesthetics. These risks include exposure to hazardous chemicals, injuries from high-tech equipment, infections, and aesthetic complications. Insufficient training and inadequate use of personal protective equipment (PPE) exacerbate the situation. The study highlights the need for regular staff training, appropriate PPE usage, and risk-based standard operating procedures (SOPs). In conclusion, implementing a risk-based OHS management system using HIRARC is crucial to ensure a safe working environment in aesthetic clinics.